DEVELOPING STUDENTS’ COGNITIVE ACTIVITY THROUGH THE ORGANIZATION OF INDEPENDENT WORK IN MEDICAL EDUCATION - Ruzakhon Nasirovna Melibayeva (Bright Mind Publishing, 2025)
The article explores the theoretical and methodological foundations, as well as the evaluation criteria, for developing students’ cognitive activity in medical education through structured independent work. The research defines cognitive, motivational, and operational-practical criteria that comprehensively assess the dynamics of professional competence formation. Based on psychological, pedagogical, and neurophysiological studies, the author substantiates the interrelation between cognitive activity, intellectual development, and professional readiness of future healthcare specialists.
Keywords: Cognitive activity, independent learning, cognitive criterion, motivational criterion, operational criterion, medical education, professional competence.